Impact of COVID-19 on healthcare services engagement: a qualitative study of experiences of people living with HIV and hypertension and their providers at two peri-urban HIV clinics in Uganda - Florence Ayebare; Godfrey E. Siu; David Kaawa-Mafigiri; Joel Senfuma; Christine Kiwala; Joanita Nangendo; Fred C. Semitala; Anne R. Katahoire (BMC Health Services Research)
Abstract Background The COVID-19 pandemic presented unprecedented complexity for health care seeking globally. Little is known on how people living with HIV (PLHIV) and other co-morbidities including hypertension accessed healthcare services in resource limited settings like Uganda. Therefore, we explored qualitatively how the COVID-19 pandemic which was characterized by travel restrictions, social distancing requirements, and a heightened COVID-19 response impacted health care seeking for PLHIV and health care provision by providers in this context. We explored experiences of both PLHIV with hypertension who sought care and healthcare providers who offered HIV and hypertension services at two peri-urban HIV clinics; Kira Health center and Kisubi Hospital, in Uganda. Methods We conducted 32 in-depth interviews at two peri-urban HIV clinics in Uganda with PLHIV and hypertension and their health care providers. We sought to understand PLHIV’s experiences seeking health care services and health care providers’ experiences delivering chronic care. We used an inductive thematic analysis drawing on the socio-ecological framework to explore this research question. Results Our findings reveal that that the COVID-19 pandemic presented an extraordinary set of challenges for individuals with chronic conditions who required routine healthcare services. The Uganda government’s stringent public health measures apparently made it difficult for patients to access health care, impacted jobs, resulted in job losses, reduced income, and food scarcity. Additionally, healthcare providers prioritized COVID-19 related health services, diverting both material and human resources away from PLHIV with co-morbidities, which impacted continuity of care. Conclusion These findings highlight how the COVID-19 pandemic exacerbated PLHIV’s fragility suggesting that health systems may need support to cope with the demands of chronic care management especially during health emergencies such as pandemics. There is an urgent need to strengthen the health system in Uganda enabling resilience to deal with shocks resulting from major health outbreaks.